Evolutionary history and global spatiotemporal pattern of alfalfa mosaic virus - Gao, Yanling; Fan, Guoquan; Cheng, Shengqun; Zhang, Wei; Bai, Yanju (Frontiers in Microbiology, 2022)
The evolutionary and demographic history of alfalfa mosaic virus (AMV) is potentially quite valuable for developing efficient and sustainable pathogen management strategies. In this study, we performed worldwide phylodynamic analyses of AMV based on 154 nucleotide sequences of the coat protein gene, sampled between 1985 and 2020, to understand the epidemiology of this pathogen. Bayesian phylogenetic analysis dated the crown group of AMV to 1840 (95% credibility interval, 1687–1955). We revealed that AMV has been evolving at a rate of 4.14 × 10−4 substitutions/site/year (95% credibility interval, 1.04 × 10–4−6.68 × 10–4). Our phylogeographic analyses identified multiple migration links between Europe and other regions, suggesting that Europe played a key role in spreading the virus worldwide. Further analyses showed that the clustering of AMV isolates was significantly correlated with geographic regions, indicating that geography-driven adaptation may be a factor that affects the evolution of AMV. The results of our study might have potential implications for devising effective strategies to control this pathogen.